Evaluasi Kebijakan dan Pembelajaran Masa BDR - Astria Ayu Ramadianti (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
Currently the world is being hit by an outbreak of the corona virus which is commonly referred to as Covid-19 (Corona Virus Disease -19) which has spread to various countries including Indonesia, thus requiring various sectors to immediately take a stance in preventing wider transmission, including the education sector. In this regard, the Ministry of Education and Culture takes a firm stance through several circular letters relating to education policies in the emergency period of the spread of Covid-19. This paper examines the evaluation of policies and lessons learned during the BDR period. There are various obstacles by learning from home, both in terms of human resources, management arrangements, curriculum, and learning facilities, therefore cooperation between teachers and parents plays an important role in implementing the learning process from home in order to achieve the progress of the students themselves.